Anthozoan eDNA primer set characterizes Ctenophora and Medusozoa inhabiting mesophotic and deep waters off the Gulf Coast of the southern USA - Wood, Annemarie; McCartin, Luke; Herrera, Santiago; Quattrini, Andrea M.; Collins, Allen G. (Frontiers in Marine Science, 2025)
While gelatinous zooplankton (GZ) constitute a vital component of the marine food web, understanding their biology and ecology has been hindered because traditional collection methods often destroy their fragile bodies. Environmental DNA (eDNA) sequencing is a non-invasive approach that can detect organisms that are difficult to sample, enabling the DNA of understudied taxa to be sequenced. Here, we present the first application of eDNA metabarcoding targeting Ctenophora and Medusozoa. We first assessed the applicability of an anthozoan eDNA primer set designed to a 28S barcode in anthozoans for amplifying this region in ctenophores and medusozoans, including the creation of a 28S reference library for Ctenophora. After determining that the primers complement these groups well, the primers were used to analyze eDNA samples from mesophotic and deep-sea sites off the Gulf Coast of the southern USA. We recovered sequences belonging to a diverse array of GZ taxa and used these data to distinguish GZ communities by site and ecosystem type, characterize community diversity, and facilitate a better understanding of how these mysterious organisms interact within their ecosystem. The versatility of this primer set presents an exciting opportunity to research taxa that have been historically difficult to study, while further contributing to our understanding of their ecological roles in the deep sea.